Response to Intravenous Allogeneic Equine Cord Blood-Derived Mesenchymal Stromal Cells Administered from Chilled or Frozen State in Serum and Protein-Free Media - Williams, Lynn B.; Co, Carmon; Koenig, Judith B.; Tse, Crystal; Lindsay, Emily; Koch, Thomas G. (Frontiers in Veterinary Science, 2016)
Equine Mesenchymal stromal cells (MSC) are commonly transported, chilled or frozen, to veterinary clinics. These MSC must remain viable and minimally affected by culture, transport, or injection processes. The safety of two carrier solutions developed for optimal viability and excipient use were evaluated in ponies, with and without allogeneic cord blood-derived (CB) MSC. We hypothesized that neither the carrier solutions nor CB-MSC would elicit measurable changes in clinical, hematological, or biochemical parameters. In 9 ponies (study 1) a bolus of HypoThermosol® FRS (HTS-FRS), CryoStor® CS10 (CS10) or saline was injected IV (n=3/treatment). Study 2, following a one week washout period 5x107 pooled allogeneic CB-MSC were administered IV in HTS-FRS following 24h simulated chilled transport. Study 3, following another one week washout period 5x107 pooled allogeneic CB-MSC were administered IV in CS10 immediately after thawing. Nine ponies received CB-MSCs in study 2 and 3 and three ponies received the cell carrier media without cells. CB-MSCs were pooled in equal numbers from five unrelated donors. In all studies ponies were monitored with physical examination, and blood collection for 7 days following injection. CD4 and CD8 lymphocyte populations were also evaluated in each blood sample. In all three studies, physical exam, complete blood cell count, serum biochemistry, and coagulation panel did not deviate from established normal ranges. Proportions of CD4+ and CD8+ lymphocytes increased at 168h post injection in CB-MSC treatment groups regardless of the carrier solution. Decreases in CD4+/CD8+ double positive populations were observed at 24 h and 72 h in CB-MSC treated animals. There was no difference in viability between CB-MSC suspended in HTS-FRS or CS10. HTS-FRS and CS10 used for low volume excipient injection of MSC suspensions was not associated with short-term adverse reactions. HTS-FRS and CS10 both adequately maintain CB-MSC viability following hypothermic or frozen simulated transport, respectively. CB-MSC do not elicit clinical abnormalities, but allogeneic stimulation of CD4+ and CD8+ lymphocyte populations may occur. Future studies should include in vitro or in vivo evaluation of cell mediated or adaptive immunity to autologous, identical allogeneic, or MSC originating from additional unrelated individuals in order to better characterize this response.□